Structure and Phase Changes in Natural and Synthetic Magnesium Aluminum Spinel (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Natural spinel crystals from Ural and Pamir deposits and synthetic magnesium aluminium spinel single crystals with different stoichiometry (MgO.nAl2O3 ) grown by Verneuil method were used. The photoluminescence (PL), its excitation (PLE) and optical absorption of stoichiometric and nonstoichiometric magnesium aluminium spinel crystals containing the chromium and manganese ions and defects produced by fast neutron irradiation( fluence up to 1020cm-2, E>0.1 MeV) are investigated. The broadening of R- and N-lines takes place in synthetic stoichiometric spinel. Structure of synthetic nonstoichiometric spinels (n>1) has to be more disordered, since in addition to the site exchange the so called stoichiometric vacancies are present in the structure. The R- and N-lines broadening takes place after spinel crystals irradiation by fast neutron too. The neutron irradiation causes increasing of the spinel inversion. Furthermore the great deviation from stoichiometry leads to the local structure of α-Al2O3 formation around Cr3+ ions. The orange emission band at 570 nm is belonging to complex center “Mn2+-F+ (or F centre)”.